1999
DOI: 10.1096/fasebj.13.14.1911
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of nucleolin's role in growth and cell proliferation: new insights

Abstract: Cells require optimum protein synthetic activity in order to support cell proliferation, maintain homeostatic and metabolic integrity, and repair damage. Since growth depends on protein synthesis through ribosome biogenesis, the control of biosynthesis of ribosomes is necessarily a key element for control of growth. Nucleolin is a major nucleolar protein of exponentially growing eukaryotic cells, which is directly involved in the regulation of ribosome biogenesis and maturation. The highly conserved nucleolin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
498
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(514 citation statements)
references
References 138 publications
14
498
1
1
Order By: Relevance
“…Affinity chromatography using ADAMTS-2 as a bait and co-localization studies identified nucleolin as a potential membrane receptor for ADAMTS-2. Nucleolin was initially described as a nucleolar protein participating in the transcriptional control of ribosomal RNA genes, in ribosomes maturation and assembly, and in the nucleocytoplasmic transport of ribosomal components [40,41]. It has also been shown that nucleolin can translocate to the plasma membrane in some specific cell types such as endothelial cells and many transformed cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…Affinity chromatography using ADAMTS-2 as a bait and co-localization studies identified nucleolin as a potential membrane receptor for ADAMTS-2. Nucleolin was initially described as a nucleolar protein participating in the transcriptional control of ribosomal RNA genes, in ribosomes maturation and assembly, and in the nucleocytoplasmic transport of ribosomal components [40,41]. It has also been shown that nucleolin can translocate to the plasma membrane in some specific cell types such as endothelial cells and many transformed cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin may be involved in cleavage of rRNA, acts as a chaperone in correct folding of pre-rRNA processing, and in repression of transcription (Allain et al 2000;Hiscox, 2002;Yang et al 1994). The amount of nucleolin is stable in proliferative cells, but it undergoes selfcleavage in quiescent cells (Chen et al 1991;Hiscox, 2002) and is also involved in process of cell growth and proliferation (Hiscox, 2002;Srivastava and Pollard, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…38 Activated nucleolin is involved in various aspects of DNA and RNA metabolism 39 essential for cell proliferation. 40,41,47,48 We here demonstrate that in SCC cells EGF-induces activation of PI3K and PKC-z as well as nucleolin phosphorylation in the nucleus, and these processes require PLC-g1 and PIKE.…”
Section: Discussionmentioning
confidence: 61%
“…38 The activated nucleolin in the nucleus is fundamental to the survival and proliferation of cells. 40,41 To determine whether knockdown of PLC-g1 or PIKE altered EGF-induced nucleolin phosphorylation in human SCC cells, SCC4 cells were treated with siRNA for PLC-g1 or PIKE for 3 days and then with vehicle, EGF or fetal bovine serum for 7 min. Cells were harvested and nuclear lysates were isolated.…”
Section: Introductionmentioning
confidence: 99%